Indications and practical approach to non-invasive ventilation in acute heart failure - Masip, Josep; Peacock, W Frank; Price, Susanna; Cullen, Louise; Martin-Sanchez, F Javier; Seferovic, Petar; Maisel, Alan S; Miro, Oscar; Filippatos, Gerasimos; Vrints, Christiaan; Christ, Michael; Cowie, Martin; et al. (European heart journal, 2018)
In acute heart failure (AHF) syndromes significant respiratory failure (RF) is essentially seen in patients with acute cardiogenic pulmonary oedema (ACPE) or cardiogenic shock (CS). Non-invasive ventilation (NIV), the application of positive intrathoracic pressure through an interface, has shown to be useful in the treatment of moderate to severe RF in several scenarios. There are two main modalities of NIV: continuous positive airway pressure (CPAP) and pressure support ventilation (NIPSV) with positive end expiratory pressure. Appropriate equipment and experience is needed for NIPSV, whereas CPAP may be administered without a ventilator, not requiring special training. Both modalities have shown to be effective in ACPE, by a reduction of respiratory distress and the endotracheal intubation rate compared to conventional oxygen therapy, but the impact on mortality is less conclusive. Non-invasive ventilation is also indicated in patients with AHF associated to pulmonary disease and may be considered, after haemodynamic stabilization, in some patients with CS. There are no differences in the outcomes in the studies comparing both techniques, but CPAP is a simpler technique that may be preferred in low-equipped areas like the pre-hospital setting, while NIPSV may be preferable in patients with significant hypercapnia. The new modality 'high-flow nasal cannula' seems promising in cases of AHF with less severe RF. The correct selection of patients and interfaces, early application of the technique, the achievement of a good synchrony between patients and the ventilator avoiding excessive leakage, close monitoring, proactive management, and in some cases mild sedation, may warrant the success of the technique.